Performance of basophil activation test and specific IgG4 as diagnostic tools in nonspecific lipid transfer protein allergy: Antwerp‐Barcelona comparison. Issue 3 (7th October 2019) - Decuyper, Ine I.; Pascal, Mariona; Van Gasse, Athina L.; Mertens, Christel; Díaz‐Perales, Araceli; Araujo, Giovanna; Torradeflot, Maria; Rius, Josefina; Balsells, Sara; Muñoz‐Cano, Rosa M.; Bartra, Joan; Li, Lynne; et al.
Abstract: Background: Recent studies show that nsLTP sensitization is not limited to the Mediterranean basin and can present diverse clinical phenotypes. It remains challenging to predict clinical outcome when specific IgE antibodies (sIgE) to nsLTPs are present. This study compares both clinical and in vitro allergy characteristics but also diagnostic performance of a basophil activation test (BAT) and sIgG4 in nsLTP‐sensitized patients from Antwerp (ANT, Belgium) and Barcelona (BCN, Spain). Methods: Adult subjects with positive sIgE rPru p 3 and/or rMal d 3 ≥ 0.10 kUA /L (n = 182) and healthy controls (n = 37) were included. NsLTP‐sensitized individuals were stratified according to clinical symptoms with peach/apple, respectively. BAT rPru p 3 and rMal d 3 were performed and sIgG4 antibodies to both components quantified. Results: In BCN, only ratios of sIgG4/sIgE rMal d 3 and BAT rMal d 3 (0.001 µg/mL) can identify clinically relevant Mal d 3 sensitization (sensitivity of 60%‐63% and a specificity of 75%‐67%, respectively). In ANT, only the sIgE/total IgE rPru p 3 ratio shows added value (sensitivity 60% and specificity 83%). Finally, it appears that symptomatic patients in BCN are more sensitive to lower allergen concentrations compared to ANT. In addition, it was shown that ANT patients were more often sensitized to pollen and that specific pollen sources differed between regions. Conclusions: NsLTP‐related allergy profiles and diagnostic performance differ significantly between regions and are component‐specific, which makes extrapolation of data difficult to do. In addition, it seems that basophil sensitivity might show geographical differences. Additional research is needed to confirm these findings. Abstract : This study explores the performance of BAT, sIgE/total IgE, sIgG4 and sIgG4/sIgE ratio in Pru p 3‐ and Mal d 3‐sensitized populations from Antwerp (ANT) and Barcelona (BCN). In BCN, only ratios of sIgG4/sIgE rMal d 3 and BAT rMal d 3 can identify clinically relevant Mal d 3 sensitization, whereas in ANT, only the sIgE/total IgE rPru p 3 ratio shows added value. NsLTP sensitization and diagnostic performance cannot be extrapolated from one population to another. BAT, basophil activation test; nsLTP, nonspecific lipid transfer protein.